Degree of simplicity of Floquet states of a periodically driven Bose-Hubbard dimer - Steffen Seligmann; Martin Holthaus (Physical Review Research)
We investigate numerically computed Floquet states of a Bose-Hubbard dimer that is subjected to strong, time-periodic forcing with respect to their coherence, invoking a measure for their degree of simplicity previously suggested by Leggett. This serves to ascertain the validity of the mean-field approximation under conditions such that the time-dependent nonlinear Gross-Pitaevskii equation has chaotic solutions. It is shown that for sufficiently large particle numbers the exact N-particle Floquet state semiclassically associated with the innermost quantized invariant tube surrounding a stable periodic mean-field orbit represents a macroscopically occupied single-particle state, i.e., a Floquet condensate.